Inhibition of EZH2 and immune signaling exerts synergistic antitumor effects in chronic lymphocytic leukemia - Chartomatsidou, Elisavet (Blood Adv, 2019)
Microenvironmental stimuli affect EZH2 expression and function in CLL. Combined B-cell signaling and EZH2 inhibition showed synergistic effects on primary CLL cells.